Screening forage and browse legumes germplasm to nutrient stress: II. Tolerance of Lablab purpureus L. to acidity and low phosphorus in two acid soils - Mugwira, L.M.; Haque, I. (Informa UK Limited, 1993)
Although lablab (Lablab purpureus L.) is grown in many parts of Africa relatively little investigation has been done on its adaptation to acid soils, which are generally low in available In the present study, lablab was evaluated for tolerance to acidity and low available P on two Ethiopian soils. The two soils were a Nitosol (Soddo soil) and clay loam with 77 percent Al saturation (Chencha Soil). The PH of the Soddo soil unlimed was 4.8 and 5.6 when limed and with 0 and 37.5 mg/P/kg soil applied at each lime rate. The treatments on the Chencha soil were PH 4.1 and 5.9 with combinations 0 and 25 mg/P/kg added. There were highly significant differences between the mean shoot and root dry matter yields and the shoot/root ratios of the lablab accessions on the two soils as well as plant height on the Chencha soil. The mean shoot and root dry matter yields were increased by liming alone by 14 and 23 percent, while P application increased growth by 8 and 12 percent, respectively. Lime and P together suppressed mean root yields. On the Chencha soil, lime increased shoot and root yields by 87 and 35 percent, and by 58 and 14 percent with P added, respectively, while P alone increased growth by 28 and 17 percent with little effect on the limed soil. Labla could be screened for differential performance using mean dry matter yields on both soils but screening for varying levels of acidity and P was reliable only with root yield on the Soddo soil and plant height on the Chencha soil.